(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current research aimed at investigating the challenges of utilizing the social networks in Higher Education from the viewpoints of the university staff members. The questionnaire validity and reliability were assured, and it was administered to (350) university staff members in Imam Abdulrahman Bin Faisal University. The results of the statistical analysis showed that there are five main challenges that hinder utilizing the social networks in the educational process, namely, the Financial and administrative challenges, the teachers’ challenges, the learners’ challenges, the social networks challenges, and the technical challenges. The research concluded with the recommendations.